2016
DOI: 10.1097/md.0000000000005206
|View full text |Cite
|
Sign up to set email alerts
|

Optimal volume of injectate for fluoroscopy-guided cervical interlaminar epidural injection in patients with neck and upper extremity pain

Abstract: There is no study of optimal volume of contrast medium to use in cervical interlaminar epidural injections (CIEIs) for appropriate spread to target lesions. To determine optimal volume of contrast medium to use in CIEIs. We analyzed the records of 80 patients who had undergone CIEIs. Patients were divided into 3 groups according to the amount of contrast: 3, 4.5, and 6 mL. The spread of medium to the target level was analyzed. Numerical rating scale data were also analyzed. The dye had spread to a point above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Second, the volume of injectate in the parasagittal interlaminar epidural injection in the present study was decided at 6 mL arbitrarily. Although the suggested volume of injectate for epidural injection varied in a few literature reports, the optimal volume is still to be determined [35][36][37]. However, a 6 mL volume in the parasagittal approach was considered sufcient to cover the targeted spinal nerve regardless of the spinal level [38].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the volume of injectate in the parasagittal interlaminar epidural injection in the present study was decided at 6 mL arbitrarily. Although the suggested volume of injectate for epidural injection varied in a few literature reports, the optimal volume is still to be determined [35][36][37]. However, a 6 mL volume in the parasagittal approach was considered sufcient to cover the targeted spinal nerve regardless of the spinal level [38].…”
Section: Discussionmentioning
confidence: 99%
“…In horses, further study is needed to determine the optimal injectate volume to reach clinically relevant anatomy (typically lower cervical region) for the treatment of lower neck and forelimb disorders as is described in people (26).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a mixture of 2 mL of corticosteroid (betamethasone 6 mg/mL; Celestone Soluspan, Schering, Kenilworth, NJ) and 3 mL of contrast material was injected. It is established that larger volumes of contrast agent result in farther extent of spread throughout the epidural space (12)(13)(14)19,20). However, we chose 3 mL of contrast material because we felt it best reflected the volumes of medication typically delivered in clinical practice and because it was the most common volume previously examined in the planar fluoroscopy literature (11,12,14,21,22).…”
Section: Procedural Details and Ct Techniquementioning
confidence: 99%
“…Therefore, previous studies (9-14) have used planar fluoroscopic images to analyze the extent of spread of contrast agent during the CILESI epidurography as a surrogate for medication spread. These studies (9)(10)(11)(12)14) reported a wide range of rates of spread to the VES (range, 0%-93.3%). This wide variance may be because planar imaging cannot directly image contrast agent flow within the VES, which limits assessment.…”
mentioning
confidence: 99%